Distinct biological ages of organs and systems identified from a multi-omics study - Nie, Chao; Li, Yan; Li, Rui; Yan, Yizhen; Zhang, Detao; Li, Tao; Li, Zhiming; Sun, Yuzhe; Zhen, Hefu; Ding, Jiahong; Wan, Ziyun; Gong, Jianping; et al. (Cell reports (Cambridge), 2022)
Biological age (BA) has been proposed to evaluate the aging status instead of chronological age (CA). Our study shows evidence that there might be multiple “clocks” within the whole-body system: systemic aging drivers/clocks overlaid with organ/tissue-specific counterparts. We utilize multi-omics data, including clinical tests, immune repertoire, targeted metabolomic molecules, gut microbiomes, physical fitness examinations, and facial skin examinations, to estimate the BA of different organs (e.g., liver, kidney) and systems (immune and metabolic system). The aging rates of organs/systems are diverse. People’s aging patterns are different. We also demonstrate several applications of organs/systems BA in two independent datasets. Mortality predictions are compared among organs' BA in the dataset of the United States National Health and Nutrition Examination Survey. Polygenic risk score of BAs constructed in the Chinese Longitudinal Healthy Longevity Survey cohort can predict the possibility of becoming centenarian. [Display omitted] •Constructing biological ages of organs/systems using multi-omics features•Organs and systems are aging at different rates•Specific biological age could predict disease of corresponding organs•Biological ages of organs and systems have diverse genetic architectures Nie et al. estimate biological ages of organs and systems using 402 multi-omics features from 4,066 individuals and demonstrate several applications. They find that organs and systems are aging at different rates, and biological ages could be utilized for population stratification, mortality prediction, and phenotypes of genetic association studies.